The Effectiveness of Barman Model in Acquiring ‎Jurisprudential Concepts and Developing High-level ‎Thinking in Islamic Education - Najadat, Ahmed (Jordan Journal of Educational Sciences, 2021)
The study aimed at measuring the effectiveness of Barman model in acquiring jurisprudence concepts and developing high-level thinking in Islamic education. To achieve the aim of the study, the researcher adopted a semi - experimental design with partial control of the experimental and control groups. The study population was represented by the tenth-grade students in the Directorate of Education of the Irbid Kasbah Brigade. The model school of Yarmouk University was chosen intentionally. The sample size was (62) students, distributed into two groups (experimental and control) equally. The researcher taught the two groups himself during the academic year (2018/2019) according to the distribution of the school administration to the lessons of jurisprudence in the teacher’s annual study plan and the study took an entire academic year to be implemented. The recearcher also prepared a test in the acquisition of jurisprudence concepts, which consisted of (50) questions of multiple choice type, The high-ranking thinking test was adopted from Mahmoud and Hussein (2019), which includes (40) questions. The results showed the effectiveness of the Barman model in the acquisition of jurisprudential concepts and the superiority of the experimental group to the control group in developing of high-level thinking skill in Islamic education